Support for life in prison without the possibility of parole among death penalty proponents - Vogel, Brenda L. (American journal of criminal justice, 2003)
Past research provides a fairly consistent portrait of the death penalty supporter. However, when offered an alternative to death, such as life in prison without the possibility of parole (LWOP), support for the death penalty tends to diminish. Unfortunately, very little is known about death penalty proponents who support the LWOP option. This study compares death penalty supporters who favor the LWOP alternative with death penalty supporters who oppose this option. Income significantly influences LWOP opinions. The implications of these results and suggestions for further research are discussed.